Forest-Derived Actinomycetes from Indonesian National Parks: A Novel Approach for Bacterial Leaf Blight Control in Rice - Giyanto Giyanto; Ruly Anwar; Muhamad Hidayanto; Syahri Syahri (Caraka Tani: Journal of Sustainable Agriculture, 2026)
The potential of forest-derived actinomycetes from Indonesian national parks for managing bacterial leaf blight (BLB) remains largely unexplored. This study aimed to evaluate the biocontrol potential of forest-derived actinomycetes from Kutai National Park against Xanthomonas oryzae pv. oryzae and to assess their ability to promote rice seed germination, seedling vigor, and root colonization. A total of 12 actinomycete isolates were screened for in vitro antagonism against Xoo race 8. Further investigation in planta revealed that 3 isolates (KrK1K1, DrK1T20, and DrK1T21) significantly reduced disease severity by 77.77%, 86.74%, and 82.85%, respectively. Molecular identification of the 3 potential isolates revealed that KrK1K1, DrK1T20, and DrK1T21 are identified as Streptomyces parvulus, Tsukamurella tyrosinosolvens, and Salinispora tropica, respectively. Three selected isolates also significantly (p < 0.05) enhanced the seed germination rate (25.05%) and the vigor index (51.11%). Filtrate bioassays at 5%, 10%, and 15% concentrations demonstrated that only T. tyrosinosolvens DrK1T20 effectively inhibited Xoo growth. All 3 isolates produced siderophores and chitinase, whereas phosphate-solubilizing activity was detected only in S. parvulus. Scanning electron microscopy confirmed effective colonization of rice roots by actinomycetes, indicating a successful interaction between the roots and the actinomycete isolates. These abilities strongly support the potential of forest-derived actinomycetes to control BLB and improve plant growth in the field.